The Effect of Emotional Intelligence and Compensation on Employee Performance Mediated by Job Satisfaction - Aprillova, Carmelita Virry Clarissa; Liana, Lie (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of emotional intelligence and compensation on employee performance mediated by job satisfaction. This study uses a quantitative approach with a population of 80 employees of PT. Hanazono Engineering Indonesia. Data were processed using SPSS software version 26. Data analysis techniques include respondent descriptions, variable descriptions, validity tests, reliability tests, F tests, R2 tests, t tests, and Sobel Tests. The results of the study state that emotional intelligence has a positive effect on job satisfaction, compensation has a positive effect on job satisfaction, emotional intelligence has a positive effect on employee performance, compensation has no effect on employee performance, job satisfaction has a positive effect on employee performance, job satisfaction mediates the effect of emotional intelligence on employee performance, and job satisfaction mediates the effect of compensation on employee performance.